Kinerja Keuangan terhadap Profitabilitas pada Perusahaan Pertambangan di Bursa Efek Indonesia - Ida Zuraidah; Rosalina Ghozali (Jurnal Bisnis, Manajemen, dan Ekonomi, 2021)
This study uses panel data, using multiple linear regression for statistical data processing. This study aims to analyze the effect of Working Capital Turnover (X1), Firm Size (X2), Liquidity (X3), Leverage (X4) on profitability (Y) in mining companies on the Indonesia Stock Exchange (BEI) 2015-2019. Statistical calculations produce a regression equation Y = -0.006571 + 0.000812X1 - 0.000143X2 + 0.036545X3 - 0.011253X4 + e. This study concludes first, Working Capital Turnover does not have a significant positive effect on profitability. Second, Firm Size does not have a significant negative effect on profitability. Third, liquidity has a significant positive effect on profitability. Fourth, Leverage does not have a significant positive effect on profitability of mining companies on the Indonesia Stock Exchange (IDX). Fifth, Working Capital Turnover, Firm Size, Liquidity, Leverage together, positively and significantly affect profitability (Y) in mining companies on the Indonesia Stock Exchange (IDX). The researcher gives the first suggestion, mining companies listed on the Indonesia Stock Exchange must maintain the stability of their financial performance, if necessary, increase their working capital, firm size, liquidity and leverage in order to maintain and increase the company's profitability. Second, shareholders of Mining Companies listed on the Indonesia Stock Exchange do not immediately withdraw their shares when the share price drops, because it is hoped that stability will not take too long and working capital, firm size, liquidity and leverage will increase again so that they can increase the